2018
DOI: 10.1515/npprj-2018-3009
|View full text |Cite
|
Sign up to set email alerts
|

Strong paper from spruce CTMP – Part II: Effect of pressing at nip press temperatures above the lignin softening temperature

Abstract: The main objective of the current study was to demonstrate that it is possible to enhance strength properties of sheets from spruce HT-CTMP and CTMP furnishes up to the same level as is common on sheets from softwood kraft pulps by changing conditions in papermaking. To achieve that, sheets of spruce HT-CTMP and CTMP were consolidated at densities close to that of the reference bleach kraft pulp by pressing at press nip temperatures well above the tack and softening temperatures of lignin. On sheets from spruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…Interesting is that density for the HYP based samples show almost the same value, only about 10% lower, as for the NSK based samples when pressed at 200°C. This was previously verified by Norgren and Pettersson at FSCN/Mid Sweden University (Norgren et al 2018;Pettersson et al 2017). The increase in density was about 100% for HT-CTMP, 50% for CTMP and 75% for TMP.…”
Section: The Effect Of Pressing Load and Temperature On Paper Propertiessupporting
confidence: 74%
See 3 more Smart Citations
“…Interesting is that density for the HYP based samples show almost the same value, only about 10% lower, as for the NSK based samples when pressed at 200°C. This was previously verified by Norgren and Pettersson at FSCN/Mid Sweden University (Norgren et al 2018;Pettersson et al 2017). The increase in density was about 100% for HT-CTMP, 50% for CTMP and 75% for TMP.…”
Section: The Effect Of Pressing Load and Temperature On Paper Propertiessupporting
confidence: 74%
“…This makes the HYP containing stiff fibres most suitable for press-drying. Press-drying of HYP at high temperature has been further studied by Pettersson et al andNorgren et al in 2017 and2018, and they confirm the development of strength properties due to densification and increased bonded area in the paper structure (Norgren et al 2018;Pettersson et al 2017). However, in the 1980s (Back, Andersson 1979;Back 1984;Back, Olsson 1989;Swensson 1987) investigated heat treatment and dry pressing of unbleached chemical kraft paper products, particularly linerboard with the aim to improve both dry and wet strength properties.…”
Section: Hot-pressing Since the 1920smentioning
confidence: 95%
See 2 more Smart Citations
“…A higher mould B temperature improves the MPP's Young's Modulus for both initial and after water sorption. Several studies [23,24,27] observed that a higher processing temperature allows the tensile index to be improved as it allows to have a lower WTR and swelling capacity [21,24,30].…”
Section: Mechanical Properties Depending On the Process Parametersmentioning
confidence: 99%